Layered α-MoO3nanoplates for gas sensing applications - Felix, A. A. [UNESP]; Silva, R. A. [UNESP]; Orlandi, M. O. [UNESP] (Royal Society of Chemistry (RSC), 2020)
The synthesis of α-MoO3 nanoplates with a unique well-faceted rectangular morphology produced by a polymeric solution route is presented. This versatile chemical route allowed the growth of layered nanoplates on different crystalline substrates to manufacture electronic/optoelectronic nanodevices. The α-MoO3 crystalline phase was identified by both X-ray diffraction (XRD) and Raman spectroscopy. Scanning electron microscopy (SEM) and atomic force microscopy (AFM) showed that the well-faceted rectangular layered nanoplates can be obtained depending on the fine control of the synthesis parameters due to the MoO3 sublimation. Gas sensing measurements revealed that the α-MoO3 nanoplates exhibit an enhanced response to NO2, with sensor signals up to 50, combined with a low optimum operating temperature. In addition, the devices exhibited the highest selectivity to NO2 relative to H2, CO, and CH4, which can be a consequence of the specific exposed surface plane. These results reveal that layered α-MoO3 nanoplates are promising for use in the manufacturing of high-performance NO2 gas sensor nanodevices.